2009
DOI: 10.1590/s1516-44462009005000008
|View full text |Cite
|
Sign up to set email alerts
|

Food intake and serum levels of iron in children and adolescents with attention-deficit/hyperactivity disorder

Abstract: Peripheral markers of iron status and food intake of iron do not seem to be modified in children with attention-deficit/hyperactivity disorder, but further studies assessing brain iron levels are needed to fully understand the role of iron in attention-deficit/hyperactivity disorder pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 23 publications
5
49
1
Order By: Relevance
“…Moreover, the results of the case control studies searching ferritin levels differ from each other. Donfrancesco et al [18], Menegassi et al [19] and Perçinel et al [17] did not find significant differences in ferritin levels between groups. On the contrary, some other studies detected lower ferritin levels in ADHD subjects [12,44,45].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the results of the case control studies searching ferritin levels differ from each other. Donfrancesco et al [18], Menegassi et al [19] and Perçinel et al [17] did not find significant differences in ferritin levels between groups. On the contrary, some other studies detected lower ferritin levels in ADHD subjects [12,44,45].…”
Section: Discussionmentioning
confidence: 94%
“…According to parameters related to iron, CPRS total scores were not found associated with the Hb and ferritin levels in our study. Likewise, Donfrancesco et al [18], Millichap et al [43] and Menegassi et al [19] showed no significant relationship between ferritin levels and ADHD symptom scores in ADHD patients. However, Oner et al [14] found lower ferritin levels and higher CPRS, Conners' Teacher Rating Scale (CTRS) total scores in accordance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of recent studies regarding iron deficiency and ADHD have not been consistent. While some studies have reported a significant relationship between ADHD and low serum ferritin levels [16][17][18][19][20][21][22][23], others studies have reported no such relationship [15,[24][25][26][27]. Further, not all of these studies have compared the results of ADHD patients with those of healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is important to enroll patients who are not using psychotropic medications in these studies. However, only seven of the present studies on the subject involve the stimulant-naive cases [15,25,27,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%